2023
DOI: 10.1177/23998083231161612
|View full text |Cite
|
Sign up to set email alerts
|

Walking alone or walking together: A spatial evaluation of children’s travel behavior to school

Abstract: The purpose of this research is to extend our understanding of children’s walking behavior to school in an understudied region of the world, Istanbul, Turkey. Children (aged 11–17) and their parents were surveyed to comprehend subjective and objective factors on walking behavior to school when alone or with someone. Using participatory mapping and GIS, a route detour index was first created to highlight differences in walking behaviors. A robust spatial analysis, consisting of spatial statistics and a hierarch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…Srirangam et al (2023) developed a toolkit based on integrating land use with street network connectivity to make cities sustainable. Also, Rybarczyk et al (2023) employed space syntax to analyze children's walking behavior to school. They found that walkability had no influence on children's route choice decisions.…”
Section: Conceptual Structure In Space Syntax Studiesmentioning
confidence: 99%
“…Srirangam et al (2023) developed a toolkit based on integrating land use with street network connectivity to make cities sustainable. Also, Rybarczyk et al (2023) employed space syntax to analyze children's walking behavior to school. They found that walkability had no influence on children's route choice decisions.…”
Section: Conceptual Structure In Space Syntax Studiesmentioning
confidence: 99%